Conifers Recent Advances - Cristina Gonçalves, Ana; Fonseca, Teresa (IntechOpen, 2022)
Conifers include a wide range of species that are spread all over the world. These species have wide diversity, variable stand structures ranging from monospecific monocohort to multispecific multicohort, and produce an assortment of products and services, the most frequent of which is timber. This book is a collection of contributions, both reviews and research studies, from different fields and perspectives on the management, regeneration, growth, diversity, and production of conifer stands. The book also addresses the effect of wildfires on conifer ecosystems and respiratory allergies to conifers.